2012
DOI: 10.1111/j.1467-789x.2012.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure of morbidly obese patients using indirect calorimetry: a systematic review

Abstract: The increasing proportion of acutely ill hospital patient admissions presenting with a morbidly obese body mass index (BMI ≥ 40 kg m(-2) ) as a comorbidity is an emerging clinical concern. Suboptimal food intake and malnutrition is prevalent in the acute care hospital setting. The energy requirements necessary to prevent malnutrition in acutely ill patients with morbid obesity remains unclear. The aim of this systematic review was to identify studies in the literature that have used indirect calorimetry to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Fifty‐seven percent of hospitalized patients with a BMI >25 show evidence of malnutrition. Patients with a BMI >30 have an OR of 1.5 for having malnutrition ( P = .02) 450 . The reasons for the surprisingly high rate of malnutrition in obese patients may stem in part from unintentional weight loss early after admission to the ICU and a lack of attention from clinicians who misinterpret the high BMI to represent additional nutrition reserves that protect the patient from insult.…”
Section: Q Obesity In Critical Illnessmentioning
confidence: 99%
“…Fifty‐seven percent of hospitalized patients with a BMI >25 show evidence of malnutrition. Patients with a BMI >30 have an OR of 1.5 for having malnutrition ( P = .02) 450 . The reasons for the surprisingly high rate of malnutrition in obese patients may stem in part from unintentional weight loss early after admission to the ICU and a lack of attention from clinicians who misinterpret the high BMI to represent additional nutrition reserves that protect the patient from insult.…”
Section: Q Obesity In Critical Illnessmentioning
confidence: 99%
“…Recent analyses indicate that predictive equations estimated resting EE within 10% of measured rate in only 38–70% of non-hospitalized obese patients 29 and even in fewer patients when assessing hospitalized obese patients. 30,31 In general, predictive equations tend to overestimate the energy requirements in obese patients, while the Mifflin–St Jeor equation has been found to yield the closest prediction compared with measured resting EE. 29,31,32 Owing to an increasingly sedentary lifestyle as well as the vast availability of energy-dense foods, the patients of today, both inpatient and outpatient, are very different than those studied decades ago.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…30,31 In general, predictive equations tend to overestimate the energy requirements in obese patients, while the Mifflin–St Jeor equation has been found to yield the closest prediction compared with measured resting EE. 29,31,32 Owing to an increasingly sedentary lifestyle as well as the vast availability of energy-dense foods, the patients of today, both inpatient and outpatient, are very different than those studied decades ago. Predictive equations include only weight as a variable and these analyses illustrate the limitations associated with using predictive equations in samples dissimilar to those from which they were derived.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Energy requirements are difficult to define in these patients since their lean body mass, which determines the REE, may decrease, increase, or be normal, and fat may also contribute to variability in REE. In a review of the literature including 20 articles, Kee et al 32 found that the most common result for REE measured in morbidly obese but not acutely ill patients with a body mass index (BMI) between 40 and 80 kg/m 2 was between 1800 and 2600 kcal/d. These measurements are in great disparity with those derived from predictive equations 33 …”
Section: Practice Applications Of Indirect Calorimetrymentioning
confidence: 99%